2017
DOI: 10.1186/s41110-017-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energy drinks on biochemical and sperm parameters in Wistar rats

Abstract: Background: The present study evaluates the effects of energy drinks on the reproductive and biochemical parameters of adult male rats. Methods: A total of 40 male rats (Wistar) were exposed to an energy drink mixed with the drinking water for a period of 120 days. The animals were divided into four groups and exposed to increasing therapeutic doses (DT) of an energy drink, based on allometric extrapolation, resulting in values (mL/day) per animal of 250 g: DT1 2.36 mL, DT3 7.47 mL, and DT6 14.16 mL. The contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…23 On contrary Eduardo et al, observed insignificant weight gain in adult male rats after 120 days administration of caffeinated energy drink and explained the thermogenic effect of high doses of caffeine which along with gastrointestinal disturbance might be responsible for weight control. 24 Similar results were proved in a 4-week study conducted at University of Illinois that caffeine reduces body weight gain by decreasing storage of lipids and production of triglycerides. 25 However, weight gain in group C and D was less (caffeinated energy drink, 40% and 60% of flax seed oil) respectively as compared to group B (caffeinated energy drink).…”
Section: Body Weight Of the Rats (G)supporting
confidence: 64%
“…23 On contrary Eduardo et al, observed insignificant weight gain in adult male rats after 120 days administration of caffeinated energy drink and explained the thermogenic effect of high doses of caffeine which along with gastrointestinal disturbance might be responsible for weight control. 24 Similar results were proved in a 4-week study conducted at University of Illinois that caffeine reduces body weight gain by decreasing storage of lipids and production of triglycerides. 25 However, weight gain in group C and D was less (caffeinated energy drink, 40% and 60% of flax seed oil) respectively as compared to group B (caffeinated energy drink).…”
Section: Body Weight Of the Rats (G)supporting
confidence: 64%
“…The potassium that is present in jaggery is responsible for reducing cholesterol levels (Rao and Singh, 2021). The cholesterol level of the rats in the AED group was not affected because according to some authors the presence of taurine in artificial energy drinks prevents the decrease in testicular cholesterol levels (Chen et al, 2016;Schuchowsky et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…However, the decline in the quality of sperm was bound to increase in the concentration of energy drinks consumed as it was highly significant in G3, which consumed the highest concentration; this result is in accordance with the results of [31], who reported that a change in sperm morphology. Abnormal sperm morphology, number, and viability may reflect abnormality in spermatogenesis affected by the content of energy drinks [32]. Male fertility is contingent upon the presence of normal linear progressive sperm motility and normal sperm morphology.…”
Section: Discussionmentioning
confidence: 99%